Angelman Syndrome: Chromosome Abnormality - J Gordon Millichap (Pediatric Neurology Briefs, 1992)
Clinical cytogenetic and molecular evidence in 1 patient with paternal uniparental disomy (UPD) for chromosome 15 is reported from the University of Florida College of Medicine, Gainesville, FL.